Cancer-related cognitive impairment and patients' ability to work: a current perspective. Issue 1 (March 2017) - Duijts, Saskia F.A.; van der Beek, Allard J.; Boelhouwer, Ingrid G.; Schagen, Sanne B.
Abstract : Purpose of review: About half of all cancer survivors are 65 years of age or younger and potentially part of the labor force. Increasing numbers of these survivors are able to return to work (RTW) or even continue working during treatment. Many factors are known to inhibit occupational reintegration of cancer survivors, and further affect job performance after RTW. However, the impact of cancer-related cognitive impairment on work-related outcomes in cancer survivors is not well understood. Recent findings: Previous studies exploring cancer, cognition and the ability to work reported mixed results, because of inconsistency in the definitions of work-related outcomes, the use of self-reported rather than performance-based measurements and the interaction between cognitive limitations and other symptom burden, such as fatigue or job stress. In addition, a lack of interventions to specifically target cognitive problems at work was identified. Summary: Cognitive problems because of cancer diagnosis and treatment demand action in terms of developing a better understanding of their impact on the ability to work, as well as identifying effective therapeutic interventions to diminish this impact, including innovative accommodations, changes in work tasks or organization and ergonomic adjustments. Both employers and survivors should welcome such changes, to rise to the challenge of successfully adapting from the precancer status quo.